ABOUT CARRYING CAPACITY OF FLEXIBLE RETAINING WALL - and and (Municipal economy of cities. Series: «Economy science», 2013)
In the article describes sheet pile wall, retaining a multi-layer backfill taken into account the horizontal pressure of backfill on anchoring part of the wall.